Beneficial Biological Activities of Cinnamomum osmophloeum and Its Potential Use in the Alleviation of Oral Mucositis: A Systematic Review - Abu Bakar; Pin-Chuan Yao; Valendriyani Ningrum; Cheng-Tzu Liu; Shih-Chieh Lee (Biomedicines, 2020)
The aim of this review was to provide an updated overview of studies on the medical-biological activities of Cinnamomum osmophloeum (C. osmophloeum) in vitro and in vivo and the potential therapeutic use of natural agents prepared from this plant for the alleviation of oral mucositis (OM). Reported articles were collected using web search engine tools. The systematic review was organized according to the preferred reporting items for reviews and meta-analyses (PRISMA) statement. Additional sources were identified through cross-referencing to identify the potential use of C. osmophloeum in the alleviation of OM. The results disclosed that C. osmophloeum is comprised of bioactive ingredients that could act diversely as a reagent in anti-inflammation, antibacterial, antioxidant, anti-hyperglycemic, antidyslipidemia, anti-cancer, renal disease therapy and anti-hyperuricemia capacities. Recent studies revealed that the overall effects on anti-inflammation, wound repair, and the antibacterial and antioxidant activities of its constituents would act as a potential remedy for oral mucositis. Up-to-date in vitro and in vivo studies on the medical-biological activities of C. osmophloeum suggested that C. osmophloeum and its constituents could be promising remedies as adjuvants in OM therapy and warrant further investigation.